The cause of independence and the Republic. Vicente Guerrero, a Mexican rebel against the revived Spanish Constitution in 1820 - Miranda Arrieta, Eduardo (Universidad Pedagógica y Tecnológica de Colombia, 2012)
In this article the author analyzes the speech and actions of Vicente Guerrero in connection with the reestablishment of the Spanish Constitution, which in 1810 had launched a successful military action with Morelos for the takeover. The article also takes into account the ideological and political effect of the regulation (through their military delegates) on the inhabitants of the various villages near the armed conlict, So with him they could discover the persuasive activity, which made the leader of theSouth. The interest is mainly centered on the republican convictions of Guerrero, which are intended to take precedence over Cadiz constitutional persuasions to maintain and control its support forces.